Comparison of Patient-Controlled Analgesia (PCA) and Transversus Abdominis Plane (TAP) Block for Postoperative Pain Control in Patients Undergoing Abdominoplasty - Fathulla, Hevy Sherko; Shawq, Bnar Halko Ahmad; Ahmed, Hozan Abdulwahid; Farhai, Alan Ihsan (Academic Journal of Clinicians, 2023)
Background: Postoperative pain management is major priority for the surgeon and patients , so adequate pain control and choosing the correct method makes patient more stable. Aim of study: T o compare the effectiveness of TAP block and PCA for post operative pain control for patients undergoing abdominoplasty. Patient and method: A prospective comparative study conducted during the year 2023 and included 30 cases undergoing abdominoplasty in Par hospital. Patients were assigned into two equal groups to be managed by either PCA or TAP block. Written informed consent was obtained for each case and all ethical issues were taken into account and approved by the authors. Result: Both groups were almost matched for age , weight and ASA class, (P.>0.05). Systolic and diastolic blood pressure, mean arterial pressure and heart rate were significantly lowered in PCA group compared to TAP block group, (P<0.05). Pain score was significantly lowered in both groups. It was more significant and lower in PCA than TAP block group (P<0.05). Conclusion: Tap block and PCA both are efficient in relieving postoperative pain but dose and ways are different for each one. Each modality have its benefit and pitfall, so none of these two modalities is superior to other.